Health and Girlhood in Britain, 1874-1920 - Marland, H.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This first major study of girls' health in modern Britain explores how debates and advice on healthy girlhood shaped ideas about the lives of young women from the 1870s to the 1920s, as theories concerning the biological limitations of female adolescence were challenged and girls moved into new arenas in the workplace, sport and recreation.
Keywords: History; Great Britain—History.; Sociology; Social history; History, Modern; History of Science; History of Britain and Ireland; Gender Studies; Social History; Modern History